Self-assembled micro-flowers of ultrathin Au/BiOCOOH nanosheets photocatalytic degradation of tetracycline hydrochloride and reduction of CO2. (November 2021) - Ma, Chi; Wei, Jingjing; Jiang, Kainian; Yang, Zhongzhu; Yang, Xu; Yang, Kaihua; Zhang, Yi; Zhang, Chang
Abstract: The low separation efficiency of carriers and weak light response of photocatalysts severely limit the application of photocatalysis technology. Herein, we prepared a visible light responsive self-assembled micro-flowers of ultrathin bismuth oxide formate nanosheets supported by gold nanoparticles (Au/BiOCOOH) composite photocatalyst via hydrothermal method. The physicochemical and photoelectric properties of obtained-photocatalysts were completely analyzed via a range of characterization means. Compared with bare BiOCOOH, the photocatalytic activity of Au/BiOCOOH was significantly improved. 2.0%Au/BiOCOOH possessed the highest rate constant of 0.0054 min −1 for degradation of tetracycline hydrochloride (TC-HCl), which was nearly 13.5 times higher than that of BiOCOOH. The intermediate products were analyzed by 3D EEM and HPLC/MS, and the antibacterial ability of intermediate products with 2.0%Au/BiOCOOH significantly descended. In order to explore the potential of practical applications, photocatalytic experiments were also implemented through different water sources and solar light irradiation. Furthermore, the photocatalytic activity was also investigated by photocatalytic reduction of carbon dioxide (CO2 ). The excellent photocatalytic activity owed to the enhanced separation of charge carriers and light absorption ability by the surface plasmon resonance (SPR) effect of Au nanoparticles. The work may provide a feasible strategy to obtain efficient BiOCOOH-based photocatalyst. Graphical abstract: Image 1 Highlights: A novel Au/BiOCOOH photocatalyst was obtained via one pot hydrothermal process. The Au/BiOCOOH displayed excellent photocatalytic activity towards tetracycline hydrochloride degradation and CO2 reduction. The excellent photocatalytic activity of Au/BiOCOOH owned to the SPR effect of Au nanoparticles.